Opportunities for Durian Peel Flour (Durio zibethinus Murray) as an Alternative to High-Fiber Food - Rahmiwati, Anita; Ramadhani, Aulia; Deya Silviani (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
This study evaluated the effects of drying temperature and duration on the nutritional composition (carbohydrates, protein, fat, moisture, and ash) and lignocellulose content (cellulose, hemicellulose, and lignin) of durian peel flour. The inner white peel (albedo) of Durio zibethinus was washed, sliced, dried at specific temperature-time combinations, and ground into flour. A laboratory experimental design using a Completely Randomized Design (CRD) was employed using three treatments to represent variations in drying temperature and duration: P1 (60°C, 10 hours), P2 (70°C, 8 hours), and P3 (80°C, 6 hours). Data were analyzed using SPSS software with normality tests, ANOVA, and Duncan tests. The nutritional compositions of durian peel flour in P2 were 66.69% carbohydrates, 10.85% protein, 0.76% fat, 17.24% moisture, and 4.45% ash. The lignocellulose content in P2 consisted of 35.20% cellulose, 15.64% hemicellulose, and 10.90% lignin. Significant differences were found in cellulose, carbohydrate, moisture, and ash content based on drying conditions. Specifically, P2 (70°C for 8 hours) yielded the highest carbohydrate (66.69%) and cellulose (35.20%) contents while simultaneously producing the lowest moisture (17.24%) and ash (4.45%) contents compared to the other treatments. Overall, the study shows that drying at 70°C for 8 hours optimally preserves the nutritional and lignocellulose content of durian peel flour, which emphasized its potential role in developing sustainable, high-fiber functional foods or supplements. This research provides new insight into the optimization of drying conditions for transforming durian peel into a nutritionally valuable and fiber-rich flour and demonstrates how controlled thermal treatment can improve nutrient retention and lignocellulose stability.